PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DEVIDEND PAYOUT RATIO (DPR), GROWTH, UKURAN PERUSAHAAN (SIZE), KEPEMILIKAN MANAJERIAL (INSD), DAN DEBT TO TOTAL ASSET (DTA) TERHADAP NILAI PERUSAHAAN (PBV) PADA PERUSAHAAN MANUFAKTUR - Muhammad Rifqon, 12.05.52.0035; Lisiantara, Anggana (Students Journal of Accounting and Banking, 2016)
PBV is the ratio betwen stock market price and book value per share. PBV showed how far ability of firm create a relative value of the firm toward the capital invested. The higher the ratio of PBV, more successful the firm are creating a value for shareholders. This research have as a purpose to examine influence factors of return on equity (ROE), debt to equity ratio (DER), divident payout ratio (DPR), growth, firmsize, Insider Ownership and dedt to total asset (DTA) to price to book value (PBV).Â The research was conducted using purposive sampling for sampling is used and there are 74 companies that visited during the study. Analytical techniques used in the study is multiple regression analysis by using SPSS where previously the data was tested using the classical assumptions.Â The result showed that return on equity (ROE), debt to equity ratio (DER), dividend payout ratio (DPR), growth firmsize, Insider Ownership and dedt to total asset (DTA) jointly affect to price to book value (PBV.) Individually while return on equity (ROE) and dividend payout ratio (DPR) have positive relating and significant with price to book value (PBV), while debt to equity ratio and firmsize have not significant effect to price to book value.Keywords: ROE, DER, DPR, Growth, Firmsize, Insider Ownership, DTA, Price To Book Value (PBV)